Streptococcus mutans and Streptococcus dentisani in dental biofilm of children with different caries status: a pilot study - Bedoya-Correa, Claudia María; Angarita-Díaz , María del Pilar; Aristizabal Padilla, Edwin Alonso; López Jiménez, Paula Lucero; Bustamante Zapata, Julieth (Brazilian Dental Science, 2023)
Objective: Streptococcus mutans is one of the etiological agents associated with caries due to its ability to metabolize carbohydrates and resist acidic environments. On the other hand, Streptococcus dentisani, shows characteristics associated with caries control due to its ability to inhibit growth of cariogenic bacteria. The aim of this work was to quantify the levels of Streptococcus mutans and Streptococcus dentisani from dental biofilm of children related to their caries situation. Material and Methods: After identification of morphologic characteristics of reference strains was performed, clinical isolates of biofilm compatible with these strains were selected and the Polymerase Chain Reaction technique was performed using species-specific primers. Biofilm samples from 25 children with caries and 21 without caries were collected to quantify the levels of S. mutans and S. dentisani. Results: There were statistically significant differences in the levels of S. mutans in the caries group and the levels increased as the severity of the carious lesion increased. By contrast, higher levels of S. dentisani were found in the caries-free group, although no statistically significant differences were found. In addition, the levels of S. dentisani decreased as the severity of the carious lesion increased. Conclusion: The increase in the frequency of S. dentisani in the caries-free group suggests the possibility of requiring minimum levels of this species in the dental biofilm to show an actual protective effect. It must also be considered that this effect might be related to intrinsic factors in children and the intraspecies genetic variability found in every individual. KEYWORDS Biofilm; Clinical isolates; Dental caries; Streptococcus dentisani; Streptococcus mutans.